Lectotypifications in Atherospermataceae and Monimiaceae from Argentina - Martínez-Laborde, Juan Bautista; Ospina González, Juan Camilo; Zanotti, Christian (Phytotaxa, 2015)
Lectotypes for the names of one Atherospermataceae and one Monimiaceae species from Argentina are here designated.